Persistent Notochord in a Fetus with COL2A1 Mutation - Elisabeth Codsi; Brian C. Brost; Arij Faksh; Amber K. Volk; Kristi S. Borowski (Case Reports in Obstetrics and Gynecology)
Multiple anomalies including micromelia, poor mineralization of the vertebrae, and a persistent notochord were identified on second trimester ultrasound in a fetus with a COL2A1 mutation. To our knowledge, this represents the first case of a persistent notochord associated with a COL2A1 mutation in humans. In this case report, we describe ultrasound and postmortem findings and review the pathogenesis associated with a persistent notochord.